Kajian Awal Prospek Bahan Galian Monasit di Kendawangan Kalimantan Barat - Subiantoro, Lilik; Soetopo, Bambang; Haryanto, Dwi (EKSPLORIUM, 2012)
Kendawangan areas is included in the regional geological coverage area of Ketapang that is identified have monazite deposits with radioactive minerals contain is uranium (U), thorium (Th) and rare earth element (REE). Results of grain counting analysis shows the content of the mineral monazite and zircon in heavy mineral grains reached 63% to 40% (of total grains), the analysis of rock samples contained grains of 0.11% monazite. The study was conducted on secondary data covering aspects of geology, source rock, traps and interpretation of heavy mineral distribution placer contain monazite and zircon. Objectives to be obtained is information about the character of the geology and distribution of monazite mineral resources with Thorium-contain and zircon. Source rock of monazite minerals is a granite 77-150 million age (Jurassic - Late Cretaceous), including the S type of the alkaline granites, formed in pegmatitic stage which advanced differentiated at a temperature 550-6000C. The anomalous radioactivity of Granite has a value of 400 c/s-9200 c/s with the characterized minerals are K-feldspar, quartz and plagioclase, minerals accompanying the form as thorite, monazite, zircon and alanite. Uranium range of the granitic rocks is 2.5 ppm - 64.8 ppm. The lateral distribution of alluvial deposits containing monazite placer occupy at flood plains valley between of hilly land area 225,040 Ha, obeying the distribution pattern of granitic rocks. Monazite propek area lies in the valley flood plain of the watershed at Sungai Kendawangan (107,800 Ha), Sungai Airtanah dingin (27,610 Ha), Sungai Tapah (42,010 Ha) dan Sungai Naning (45,010 Ha).The potential is area target to ore deposit prospection at the next stage field investigation.